Cultura juvenil incide en el aprendizaje del idioma inglés en los estudiantes de 1 de bachillerato contabilidad de la unidad educativa “Procer José de Antepara”, del cantón Vinces, provincia de los Ríos, año lectivo 2017-2018 - Jiménez Morejón, Romario Oswaldo (2017)
The learning of the foreign language in the last time times has not been taken into account by the students since, the majority of them believe that learning the language is unnecessary for them, since they believe that it is not serve to nothing acquire the knowledge, from there arises, The importance of building new knowledge.The following project is related to the incident of the juvenile cultures in student learning, diminishing the interest to learn the language and giving a negative effect on the academic performance. By which the research is realized to announce the problems that they presented in the institution.The creation of playful activities as a strategy to combat the influences of the juvenile cultures in the learning students, constitutes a fundamental base for achieve the necessary concentration, to acquire useful knowledge within the teaching-learning process.The proposal is realized on the basis of activities of motivation, games and dynamics where teachers and students using the activities to strengthen teaching and learning English in the classroom, will also encourage the use of activities to prevent cultures The better the performance of students.